Role of diffusion weighted MRI in characterization of renal diseases - Kumar, Pankaj; ., Yashpaul; Soni, P. K.; Kapoor, Dhiraj; Kumar, Rajesh; Malakar, Sayan; Singh, Guriqbal; Dass, Bhagwan (International Journal of Advances in Medicine, 2018)
Background: MRI has the unique ability to show both structure and function objectively without any radiation exposure to the patient. Apparent diffusion coefficient (ADC) is a quantitative parameter that combines the effects of capillary perfusion and water diffusion. Renal parameters have shown inverse relationship with the ADC values in these studies. So, ADC values have a potential to serve as a marker of renal function. The aim of the present endeavor was to study the role of DW MRI in characterization of renal function and to find out the clinical use of DW MRI in renal diseases; and establish the relationship between renal function assessed by eGFR and that by DW MRI calculated in terms of ADC values in various renal diseases Methods: Total 30 patients were included in the study. The study was carried out in department of radiodiagnosis at Dr. RPMGC Kangra. 1.5 Tesla MRI machine was used. The ADC value was calculated at upper, mid and lower pole of each kidney and the mean was taken. Then the mean of right and left kidneys was taken to calculate the mean ADC of the patient. Results: Serum creatinine in present study ranged from 0.67 to 13.9mg/dl, with mean value of 7.28mg/d. Serum urea ranged from 22 to 293mg/dl with the mean of 119.6mg/dl. There was significant inverse correlation occurred between ADC values and serum urea (r=-0.43, p=0.02). There was significant inverse correlation between ADC values and serum creatinine (p=0.01) and a positive correlation between eGFR and ADC values (r=0.14, p=0.47). Conclusions: ADC values consistently decreased with increasing stage of renal failure, so these can be used as an indirect maker of renal function. Authors conclude that lower would be the ADC value more advanced would be the stage of renal failure. DW MRI can also be detect early stages of renal failure even when the serum maker are within normal range.